Colorimetric and photometric characterisation of clear and coloured pavements for urban spaces. Issue 5 (4th May 2021) - Autelitano, Federico; Maternini, Giulio; Giuliani, Felice
Abstract : A widespread use of clear and coloured pavements was internationally encouraged in recent years for different urban spaces. Unlike traditional "black" pavements, the design of the appropriate colour and visibility represent key factors for these wearing courses in environmental and monumental valuable contexts, where the aesthetic and the appearance of the finished layer represent essential characteristics. Operational methodologies and experimental measurements for the colorimetric and photometric characterisation of coloured pavements were presented. Due to cost consideration, thin pigmented slurry seals produced with two different clear synthetic emulsions and three inorganic pigments (red, green and blue) were taken into account. Physical parameters were monitored both at the construction phase and after an accelerated laboratory weathering, to evaluate the UV photo-oxidative effects. The obtained results highlighted three main findings: importance of a correct mix design, progressive colour change over UV exposition time and possible conversion of photometric parameters measured with different instruments.